Exploring Mental Health in Justice Involved Youth: Relevance for Policy and Practice - MacLellan, Angelina Sarah (2017)
Over the past two decades, awareness of the prevalence of mental health problems in young offenders (ages 12 to 17 years) has grown, with estimates suggesting significantly higher rates compared to the general population. While experiencing poverty does not cause crime, recent research drawing from the Social Psychology of Crime suggests that individuals who experience poverty tend to live in adverse social environments, which can facilitate exposure to modeling and/or reinforcement that is related to antisocial behaviour. In the present study, archival data were drawn from 281 young offenders’ files from an urban-based court clinic to examine how the youth’s socioeconomic and mental health status and offending history interacts, to inform how services can be offered to best suit the needs of these youth. From the current study, over three quarters of a court clinic sample had at least one mental health diagnosis, with over half reporting at least two separate diagnoses. One in five of the offenses that were committed by a youth leading to their court clinic referral were directly related to a mental health disorder. A larger proportion of youth who live in moderate to high levels of poverty were more likely to have experienced persistent mental health concerns. These findings are discussed as they relate to intervention strategies for youth and their families